Low threshold for cutaneous allergen sensitization but no spontaneous dermatitis or atopy in FLG-deficient mice - Muhandes, Lina; Chapsa, Maria; Pippel, Martin; Behrendt, Rayk; Ge, Yan; Dahl, Andreas; Yi, Buqing; Dalpke, Alexander; Winkler, Sylke; Hiller, Michael; Boutin, Sébastien; Beissert, Stefan; et al. (The journal of investigative dermatology, 2021)
Loss of FLG causes ichthyosis vulgaris. Reduced FLG expression compromises epidermal barrier function and is associated with atopic dermatitis, allergy, and asthma. The flaky tail mouse harbors two mutations that affect the skin barrier, Flgft, resulting in hypomorphic FLG expression, and Tmem79ma, inactivating TMEM79. Mice defective only for TMEM79 featured dermatitis and systemic atopy, but also Flgft/ft BALB/c congenic mice developed eczema, high IgE, and spontaneous asthma, suggesting that FLG protects from atopy. In contrast, a targeted Flg-knockout mutation backcrossed to BALB/c did not result in dermatitis or atopy. To resolve this discrepancy, we generated FLG-deficient mice on pure BALB/c background by inactivating Flg in BALB/c embryos. These mice feature an ichthyosis phenotype, barrier defect, and facilitated percutaneous sensitization. However, they do not develop dermatitis or atopy. Whole-genome sequencing of the atopic Flgft BALB/c congenics revealed that they were homozygous for the atopy-causing Tmem79matted mutation. In summary, we show that FLG deficiency does not cause atopy in mice, in line with lack of atopic disease in a fraction of patients with ichthyosis vulgaris carrying two Flg null alleles. However, the absence of FLG likely promotes and modulates dermatitis caused by other genetic barrier defects.
Gesehen am 29.01.2022